2004
DOI: 10.1007/s00595-004-2744-2
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Schwannoma of the Pancreas: Report of a Case

Abstract: We report a case of pancreatic melanotic schwannoma mimicking an epithelial cystic neoplasm of the pancreas. A 67-year-old Japanese woman underwent routine ultrasonography, which showed a large cystic mass in the head of the pancreas. Contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI) showed an inhomogeneous, round cystic mass, which was encapsulated, in the head of the pancreas. We performed pyrolus-preserving pancreatoduodenectomy under the tentative diagnosis of a cystic neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…(See Table 1. [31][32][33][34][35][36][37][38][39][40][41] In conclusion, we present a case of an 8-cm pancreatic schwannoma characterized by cystic degeneration, which was asymptomatic and was diagnosed incidentally while an examination was performed for an ovarian teratoma. Although pancreatic schwannoma is a rare benign disease, it should be included in the list of differential diagnoses of pancreatic mass with cystic changes.…”
Section: Discussionmentioning
confidence: 99%
“…(See Table 1. [31][32][33][34][35][36][37][38][39][40][41] In conclusion, we present a case of an 8-cm pancreatic schwannoma characterized by cystic degeneration, which was asymptomatic and was diagnosed incidentally while an examination was performed for an ovarian teratoma. Although pancreatic schwannoma is a rare benign disease, it should be included in the list of differential diagnoses of pancreatic mass with cystic changes.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] In 1990, Carney 7 noted the very frequent (B50%) association of MS with other stigmata of Carney complex (skin pigmentary abnormalities, myxomas, endocrine tumors, or endocrine overactivity). Since then, <200 cases, most often occurring in the paraspinal nerve roots and gastrointestinal tract, have been described, chiefly in the form of case reports or small series.…”
mentioning
confidence: 99%
“…The most common reasons for nonenucleation were that it was difficult to separate tumors from the peritumor vessels or tissues, including the portal vein, superior mesenteric vessels, or normal pancreas, and the possibility of malignancy was not excluded. 1,[3][4][5][6]9,12,17 In conclusion, abdominal pain was not dependent on the size of the BSPH and was likely 1 of the earlier signs of the BSPHs. Abdominal US was not enough to detect the small schwannomas in the head of the pancreas.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] One-half of the 22 patients had tumors located in the pancreatic head. Several reports showed that simple enucleations of benign tumors in the pancreatic head were feasible, safe, and recommended if possible.…”
mentioning
confidence: 99%